Ask The Experts: Critical issues in cancer pain management. (May 2012) - Sabatowski, Rainer
Rainer Sabatowski qualified as anesthesiologist in 1995 and as pain specialist in 2003. He was head of a pain clinic at the University of Cologne, Germany, from 2002 to 2007. Since 2007 he has been head of the Comprehensive Pain Center at the University Hospital "Carl Gustav Carus" at the Technical University Dresden (Germany). This is an integrated center with a focus on cancer pain management in cooperation with the Comprehensive Cancer Center (UCC) and multimodal programs for the treatment of chronic noncancer pain patients. He performed several studies on the topic of the impact of opioids on cognitive and psychomotor function and worked as an external consultant of the European Driving under the Influence of Drugs, Alcohol and Medicines (DRUID) project. Currently his team works on – among other topics – spouses' impact on the chronification processes in noncancer pain patients and on the implementation and evaluation of multimodal pain management programs for different pain populations, as well as in different clinical settings. He has spoken at many national and international pain meetings and was scientific chair of the 8th Palliative Care Congress of the German Society of Palliative Care in Dresden in 2010. He has published over 100 papers and book chapters and is on the editorial board of several pain journals. He is also a member of the advisory board of the German IASP chapter and works in several focus groups of this pain society.